Electrochemical Corrosion of Ag Electrode in the Silver Grid Electrode‐Based Flexible Perovskite Solar Cells and the Suppression Method (Solar RRL 9∕2018). Issue 9 (7th September 2018) - Wang, Jie; Chen, Xiaolian; Jiang, Fangyuan; Luo, Qun; Zhang, Lianping; Tan, Mingxi; Xie, Menglan; Li, Yan‐Qing; Zhou, Yinhua; Su, Wenming; Li, Yuanjie; Ma, Chang‐Qi
Abstract : In article no.1800118, Qun Luo, Yinhua Zhou, Wenming Su, Chang‐Qi Ma, and co‐workers show that the PH1000 (highly conductive PEDOT:PSS) involves electrochemical corrosion of the Ag electrode in flexible Ag grid electrode‐based perovskite solar cells. Such corrosion is suppressed by introducing polyethylenimine (PEI) in the PH1000 layer because of the reduction of PH1000 by PEI prior to Ag.